PRA RANCANGAN INSTALASI PENGOLAHAN AIR LIMBAH (IPAL) TAMBAK UDANG SISTEM SEQUENCING BATCH REACTOR KAPASITAS 325 M3/HARI (Studi Kasus Kawasan Pesisir Pantai Kabupaten Kebumen Jawa Tengah) - Purnawan _; Hadi Prasetyo Suseno; Maega urfadhilah (IST AKPRIND Yogyakarta, 2018)
The south coast of Java area which is known as barrend land and has no economic value for agricultural land, this area has big potential for aquaculture like shrimp farm, and from 2001 pilot project shrimp farm expanded to two districts in Central Java namely Kebumen Districts and Purworejo Districts (Dwi, 2017). Based on data from Kebumen Regional Agency for Integrated Licensing Services Investment Board, in 2016 there were 300 shrimp farms scattered in several sub-districts and villages (http://www.kebumenekspres.com/2016/).As one of the activities in the coastal mainland, pond fishery management are often lack of attention about natural resources capabilities with preservation of ecosystems and environment (Yustiningsih, 1996, dalam Libriyanto, 2008). Feeding rate used in shrimp ponds generate organic waste that can pollute the aquatic system (Hongsheng et al, 2008 dalam Fahrur et al, 2016).According to the Decree of the Minister of Maritime Affairs and Fisheries No: Kep. 28/MEN/2004 about general instruction shrimp cultivation in ponds, some parameters that require management BOD, NH3 dan PO4. The planned processing alternatives in this pre-designed consist of Sequencing Batch Reactor, anaerobic biofilter,basin of water collectors that functions as well chlorination tub and mud dryer tub. The test results of characteristics of shrimp pond wastewater parameters BOD5 : 152,87 mg/L, NH3 : 25,25 mg/L , PO4-3 : 1,0578 mg/L with processing capacity 325 m3/day requires land area 232,41 m2 and Calculation of the cost budget plan based on the price of the work unit (HSPK) Kebumen Region 2016 generate a total cost of Rp. 328.951.329,-